RETREAT: A REal-Time TREmor Analysis Tool for Seismic Arrays, With Applications for Volcano Monitoring - Smith, Patrick J.; Bean, Christopher J. (Frontiers in Earth Science, 2020)
Volcanic tremor is a sustained seismic signal associated with volcanic unrest and is often linked to movement of magmatic fluids in the subsurface. However, signals with similar spectral content can be generated by other surface processes. Hence, one of the best ways of distinguishing between different possible mechanisms is by tracking the location of its source, which is also important for mitigating volcanic risk. Due to its emergent nature, tremor cannot be located using travel-time based methods, and therefore alternatives such as amplitude-based techniques or array analysis must be used. This work presents a python-based software tool that uses array data and array processing techniques to analyze and locate volcanic tremor signals. RETREAT utilizes existing routines from the open-source ObsPy framework to carry out analysis of seismic array data in real-time and performs f-k (frequency-wavenumber) analysis, or Least-Squares beamforming, to calculate the backazimuth and slowness in overlapping time windows, which can help track the location of volcanic tremor sources. A graphical or web-based interface is used to configure a set of input parameters. These include settings for configuring the data source, pre-processing, timing and update options as well as parameters for the array analysis. Once configured, the tool fetches chunks of waveform data in real-time and updates accordingly. On each update the tool returns plots of the array processing results as well as plots of the waveform, envelope and spectrogram. The array response function, a histogram of the power and a map of the array with dominant backazimuth overlaid can also be produced. The tool has been tested using real-time data from the small aperture SPITS array in Spitsbergen, as well as on data from an array deployed during the 2014 eruption of Bárðarbunga volcano, Iceland. Configuration files and waveform data for these examples are supplied with the distribution. RETREAT can also be used for infrasound and has been tested on infrasonic array data recorded at Mt. Etna, Italy. RETREAT is intended for use in real-time monitoring settings and it is hoped it will facilitate greater use of arrays in tracking volcanic tremor sources in real-time, thereby enhancing monitoring capabilities.